Hike strong : the complete guide to building mountain strength, endurance, and confidence for hiking and backpacking - Appleton, James, 1986- (Falcon guide., 2026)
"In addition to finding training programs to hiking and backpacking that combine strength building, conditioning, balance and mobility, readers will learn the "why" and "how" behind these programs." -- Back cover